Synthesis and Characterization of Gold Nanoparticles by Aluminum as a Reducing Agent (Baghdad Science Journal, 2020)
The synthesis of nanoparticles (GNPs) from the reduction of HAuCl4 .3H2O by aluminum metal was obtained in aqueous solution with the use of Arabic gum as a stabilizing agent. The GNPs were characterized by TEM, AFM and Zeta potential spectroscopy. The reduction process was monitored over time by measuring ultraviolet spectra at a range of λ 520-525 nm. Also the color changes from yellow to ruby red, shape and size of GNP was studied by TEM. Shape was spherical and the size of particles was (12-17.5) nm. The best results were obtained at pH 6.